Comparison of muscle activation imbalance following core stability or general exercises in nonspecific low back pain: a quasi-randomized controlled trial - MohammadBagher Shamsi; Maryam Mirzaei; Mohammad HamediRad (BMC, 2020)
Abstract Background Low back pain causes changes in muscle activation patterns. Knowing how different exercises may improve altered muscle activation is useful in the treatment of patients. The aim of the study was to investigate whether there was a difference in the pattern of muscle activation in chronic nonspecific low back pain sufferers following core stability exercise (CSE) and general exercise (GE). Methods Fifty-six non-specific chronic LBP subjects were randomly assigned to either groups (28 participants in CSE and 28 in GE group). Both groups performed 16 sessions of an exercise program for about 5 weeks. Pain, disability and trunk muscle activation patterns (using surface electromyography) were measured at baseline and post-training. Results After the intervention period, antagonist coactivation ratio did not change in either groups. Though all compensated imbalance ratios (residual unequal muscular activity after cancellation of directionality) decreased towards negative (imbalance to left side) only this change for total muscles ratio in GE was significant (mean difference in GE group, 0.15; 95% CI: 0.02 to 0.28; p-value of paired t-test: 0.022); (mean difference in CSE, 0.02; 95% CI: − 0.07 to 0.11; p-value of paired t-test: 0.614).. No overall significantly decrease in uncompensated imbalance ratio (absolute imbalance values without cancellation directionality) was observed. Pain and disability decreased significantly in both groups. However, there was no difference between two groups in either of the variables after the intervention. Conclusions Both exercise programs reduced pain and disability and made or kept trunk muscle activation imbalance to the left side. The effects of two exercises on pain, disability and antagonist coactivation or imbalance ratios were not different. Trial registration This study was registered in the Iranian Clinical Trial Center with the code IRCT201111098035N1 , Registered Jan 21, 2013.